2014
DOI: 10.4103/1305-7456.130635
|View full text |Cite
|
Sign up to set email alerts
|

Forced eruption and implant site development in the aesthetic zone: A case report

Abstract: A multidisciplinary approach to develop the future implant site in the aesthetic zone was illustrated. A patient with perio-endo combined lesion at her upper central incisors was treated. Before extraction, forced eruption was performed and 12 months later, satisfactory amount of bone apposition was detected. At 2 weeks after atraumatic extraction, implants were placed and loaded with implant-supported restorations following osseous healing. Variables related to crown dimensions, periodontal/peri-implanter sof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…In cases of circumferential bone loss, as well as in cases of severe gingival recession, the orthodontic extrusion cannot ensure a vertical bone development suitable for the ideal implant placement, with complications such as bone dehiscence. From the various studies analysed [17,20,21,23,24], we can conclude that, even if the validity of the orthodontic extrusion technique has been demonstrated, there are no common guidelines that can be followed by the clinicians. On the contrary, there is agreement for the use of mild and continuous forces as well as for the importance of the stabilization period and of the overcorrection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cases of circumferential bone loss, as well as in cases of severe gingival recession, the orthodontic extrusion cannot ensure a vertical bone development suitable for the ideal implant placement, with complications such as bone dehiscence. From the various studies analysed [17,20,21,23,24], we can conclude that, even if the validity of the orthodontic extrusion technique has been demonstrated, there are no common guidelines that can be followed by the clinicians. On the contrary, there is agreement for the use of mild and continuous forces as well as for the importance of the stabilization period and of the overcorrection.…”
Section: Discussionmentioning
confidence: 99%
“…mm extrusion/month OC FB FU X-ray 0-1mm 1-2mm >2 mm H. Salama and M. Salama [10] 3m X-ray Linear 2-D Korayem et al [16] 7 m-3 y Linear 2-D Brindis and Block [6] Uribe et al [17] Kim et al [18] 5y X-ray Linear 2-D Amato et al [19] 18-61 m Linear 2-D Rokn et al [20] 4 m X-ray Linear 2-D Linear 2-D Chou et al [21] 2y X-ray Watanabe et al [22] 4y CBCT Volume 3-D Hochman et al [5] 1y CBCT Linear 3-D Keceli et al [23] 12 m Linear 2-D Alsahhaf and Att [24] Kwon et al [25] Linear 2-D 6 e Scientific World Journal Table 4: Data from the literature review in which the parameter of the stabilization times was compared (grey filled box � yes applied).…”
Section: -20gmentioning
confidence: 99%
“…As summarized by a recent systematic review of forced eruption for implant site development by Somar et al, an average of 0.5-1 mm of active extrusion per month was achieved by Chou et al and Amato et al using either a partial or full orthodontic bracket setup [39,42,43]. Keceli et al also reported successful treatment with an extrusion rate of 1 mm per week and three weeks of stabilization [44]. In these studies, the efficacy of bone augmentation ranged from 69% to 100%.…”
Section: Methodology and Efficacymentioning
confidence: 99%